Make a substitution:
![\begin{cases}u=2x+y\\v=2x-y\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Du%3D2x%2By%5C%5Cv%3D2x-y%5Cend%7Bcases%7D)
Then the system becomes
![\begin{cases}\dfrac{2\sqrt[3]{u}}{u-v}+\dfrac{2\sqrt[3]{u}}{u+v}=\dfrac{81}{182}\\\\\dfrac{2\sqrt[3]{v}}{u-v}-\dfrac{2\sqrt[3]{v}}{u+v}=\dfrac1{182}\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%5Cdfrac%7B2%5Csqrt%5B3%5D%7Bu%7D%7D%7Bu-v%7D%2B%5Cdfrac%7B2%5Csqrt%5B3%5D%7Bu%7D%7D%7Bu%2Bv%7D%3D%5Cdfrac%7B81%7D%7B182%7D%5C%5C%5C%5C%5Cdfrac%7B2%5Csqrt%5B3%5D%7Bv%7D%7D%7Bu-v%7D-%5Cdfrac%7B2%5Csqrt%5B3%5D%7Bv%7D%7D%7Bu%2Bv%7D%3D%5Cdfrac1%7B182%7D%5Cend%7Bcases%7D)
Simplifying the equations gives
![\begin{cases}\dfrac{4\sqrt[3]{u^4}}{u^2-v^2}=\dfrac{81}{182}\\\\\dfrac{4\sqrt[3]{v^4}}{u^2-v^2}=\dfrac1{182}\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%5Cdfrac%7B4%5Csqrt%5B3%5D%7Bu%5E4%7D%7D%7Bu%5E2-v%5E2%7D%3D%5Cdfrac%7B81%7D%7B182%7D%5C%5C%5C%5C%5Cdfrac%7B4%5Csqrt%5B3%5D%7Bv%5E4%7D%7D%7Bu%5E2-v%5E2%7D%3D%5Cdfrac1%7B182%7D%5Cend%7Bcases%7D)
which is to say,
![\dfrac{4\sqrt[3]{u^4}}{u^2-v^2}=\dfrac{81\times4\sqrt[3]{v^4}}{u^2-v^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B4%5Csqrt%5B3%5D%7Bu%5E4%7D%7D%7Bu%5E2-v%5E2%7D%3D%5Cdfrac%7B81%5Ctimes4%5Csqrt%5B3%5D%7Bv%5E4%7D%7D%7Bu%5E2-v%5E2%7D)
![\implies\sqrt[3]{\left(\dfrac uv\right)^4}=81](https://tex.z-dn.net/?f=%5Cimplies%5Csqrt%5B3%5D%7B%5Cleft%28%5Cdfrac%20uv%5Cright%29%5E4%7D%3D81)
![\implies\dfrac uv=\pm27](https://tex.z-dn.net/?f=%5Cimplies%5Cdfrac%20uv%3D%5Cpm27)
![\implies u=\pm27v](https://tex.z-dn.net/?f=%5Cimplies%20u%3D%5Cpm27v)
Substituting this into the new system gives
![\dfrac{4\sqrt[3]{v^4}}{(\pm27v)^2-v^2}=\dfrac1{182}\implies\dfrac1{v^2}=1\implies v=\pm1](https://tex.z-dn.net/?f=%5Cdfrac%7B4%5Csqrt%5B3%5D%7Bv%5E4%7D%7D%7B%28%5Cpm27v%29%5E2-v%5E2%7D%3D%5Cdfrac1%7B182%7D%5Cimplies%5Cdfrac1%7Bv%5E2%7D%3D1%5Cimplies%20v%3D%5Cpm1)
![\implies u=\pm27](https://tex.z-dn.net/?f=%5Cimplies%20u%3D%5Cpm27)
Then
![\begin{cases}x=\dfrac{u+v}4\\\\y=\dfrac{u-v}2}\end{cases}\implies x=\pm7,y=\pm13](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dx%3D%5Cdfrac%7Bu%2Bv%7D4%5C%5C%5C%5Cy%3D%5Cdfrac%7Bu-v%7D2%7D%5Cend%7Bcases%7D%5Cimplies%20x%3D%5Cpm7%2Cy%3D%5Cpm13)
(meaning two solutions are (7, 13) and (-7, -13))
Answer:
choice c. x = 6
Step-by-step explanation:
b(x) = (x+41, what is b—10)
it looks like b = x + 4
b = 10, then
10 = x + 4,
x = 6
Answer:
![- \frac{2}{7}](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B2%7D%7B7%7D%20)
Step-by-step explanation:
Slope formula:
![\boxed{ slope = \frac{y _{1} - y_2 }{x_1 - x_2} }](https://tex.z-dn.net/?f=%5Cboxed%7B%20slope%20%3D%20%5Cfrac%7By%20_%7B1%7D%20-%20y_2%20%7D%7Bx_1%20-%20x_2%7D%20%7D)
where (x₁, y₁) is the first coordinate and (x₂, y₂) is the second coordinate
Slope
![= \frac{ - 8 - ( - 6)}{14 - 7}](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7B%20-%208%20-%20%28%20-%206%29%7D%7B14%20-%207%7D%20)
![= \frac{ - 8 + 6}{7}](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7B%20-%208%20%2B%206%7D%7B7%7D%20)
![= - \frac{2}{7}](https://tex.z-dn.net/?f=%20%3D%20%20-%20%20%5Cfrac%7B2%7D%7B7%7D%20)
Answer:
If it has a radius of 9 then the length will be 18 and it would be a 18 by 3 shape and that's not a cube....
Step-by-step explanation:
If < 3 is 36 than the one across is also 36. You can calculate the < next to a given one, by subtracting it by 180.
A: < 1 is 36 degrees and < 4 is 144 degrees.
B: X=47
I found B by setting the values as equal and solving (In the picture).
Hope this helped!